Dampak Konfigurasi Taxiway Hotel dan Exit Taxiway Echo di Bandara Sultan Hasanuddin Makassar - Susanto, Agus (Airman: Jurnal Teknik dan Keselamatan Transportasi, 2018)
The number of aircraft movements at an airport that has increased every year will affect service both to the airlines and to passengers. Sultan Hasanuddin International Airport Makassar has Runway 03-21 with exit taxiway Delta, Echo, Foxtrot, Golf and Hotel. This terminal works so that the plane quickly leaves the run way. To the five exit taxiway models Echo, Foxtrot and Hotel are perpendicular to the runway so that it requires longer time than Echo and Golf rapid exit taxiway models. The aim of the study was to calculate the average taxi holding time at taxiway hotels. The research method takes a sample of the number of aircraft experiencing taxing holding time. It is recommended to accelerate the construction or reconstruction of the Echo Taxiway exit Taxiway with a rapid exit taxiway model.